2004
DOI: 10.1002/j.2161-4296.2004.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Integrated Electro-Optical Navigation Systems

Abstract: Performance is analyzed for an airborne tightly coupled inertial navigation system (INS)/GPS/electro‐optical imaging (EO) system that simultaneously estimates platform states, sensor biases, and unknown ground object coordinates using a single Kalman filter. Analysis is done by (1) comparing the performance of the INS/GPS/EO system with that of conventional tightly coupled INS/GPS navigation systems, (2) changing INS and GPS performance to determine the dependency on individual sensor performance, and (3) inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…While most existing approaches are only loosely coupled with odometery, an integration of 2D laser scans with GPS in the range-domain (generally referred to as tight coupling) is reported in [10]. Tight coupling of GPS, INS and an electro optical (EO) sensor is reported in [11].…”
Section: Figure 1 Navigation Of a Uav In An Urban Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While most existing approaches are only loosely coupled with odometery, an integration of 2D laser scans with GPS in the range-domain (generally referred to as tight coupling) is reported in [10]. Tight coupling of GPS, INS and an electro optical (EO) sensor is reported in [11].…”
Section: Figure 1 Navigation Of a Uav In An Urban Environmentmentioning
confidence: 99%
“…To estimate the rotation matrix, a minimum of two non-parallel planar surfaces is required. It can be shown that equation (10) results in the least squares estimate of C^k* ) l) .…”
Section: Cfcy(t K )-N(t W ) (8)mentioning
confidence: 99%
“…Rather scarce investigations concerning image processing are focussed only on automation of the process of keeping the ship along the water path axis, on line towards a navigation mark, in a given navigation light sector, assessment of accuracy in determining navigational parameters by using CCD camera as well as optical methods for anti-terroristic protection of ships [2,3,4,5,6,7,9,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…The processes described here complement the work of other groups developing navigational systems based on processed imagery. The authors' research group currently is researching automated imagery-based navigation system for vessels sailing along a track or a coastline (Hoshizaki et al, 2004;Snyder et al, 2004;Ryynanen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%